Coal Mines Regulation Act, 1887, Amendment (no. 2) Bill - Miners' Federation of Great Britain
House of Commons, Tuesday, July 14th, 1896. Standing Committee on Trade, Shipping and Manufactures. - Transcript from the shorthand notes of Messrs. J. Moore and Son,...